Provenance of soil parent materials in relation to regional environmental changes in the Songnen Plain, Northeast China - Shi, Yonghui; Yang, Fei; Long, Hao; Rossiter, David G.; Zhang, Aimin; Zhang, Ganlin (Geoderma Regional, 2024)
Parent materials have a strong control on soil formation process and soil properties, understanding their provenance can provide important information for soil genesis, classification, and regionalization. The Songnen Plain in northeast China has large areas of Phaeozems and Chernozems, popularly known as “black soils”, but their parent material provenance and sedimentary processes are still unclear. Therefore, this paper analyzes the types and formation process of soil parent materials in the context of regional environmental changes. This analysis is based on the characteristics of grain size distribution and quartz particle morphology at the regional and profile scales. The results indicate that aeolian loess is the predominant parent material. For instance, the surface of quartz particles exhibits characteristics indicative of mechanical impact, which is produced during the process of wind transportation. The particle size distribution curve displays a bimodal pattern, and the soil particle size tends to become finer from west to east. However, in some areas, the soil is influenced by river or lake sediments. The main source areas of aeolian deposits are likely the Gobi and sandy land in the upwind direction of the study area, while the Songhua River alluvial deposits only provide source material in local areas. High-resolution grain size analysis and K-feldspar single-particle OSL chronology show that from the Last Glacial Maximum to the Early Holocene, far-source materials dominated the deposition process. In the Middle Holocene, climate warming increased the frequency of dust activities and accelerated the deposition process. In the late Holocene, climate fluctuations and intensified human activities led to more intense dust storms in the provenance area, which in turn promoted the continuous accumulation of parent materials for soils that developed into Phaeozems and Chernozems.